Accounting Students’ Self-Efficacy in Academic English Skills: Implications for English for Accounting Instruction - Suharti - Siradjuddin (Universitas Negeri Makassar, 2026)
Purpose: This study aims to examine accounting students' self-efficacy in academic English skills and to highlight its pedagogical implications for English for Accounting instruction in higher education. Given the central role of English in accessing academic content and engaging in discipline-specific communication, understanding students' perceived capabilities across language skills is essential for designing responsive and effective instruction. Method: the study adopts a quantitative survey approach to capture students' perceptions of their academic English self-efficacy. Data were gathered through a structured questionnaire administrated to undergraduate accounting students enrolled in professional accounting-related programs. The analysis focused on identifying general patterns of self-efficacy across the core academic language skills of listening, speaking, reading, and writing, using descriptive analytical procedures to interpret students'responses. Findings: The findings indicate that students'self-efficacy in academic English is not uniform across skills. Receptive skills, particularly listening, tend to be associated with higher levels of perceived confidence, while productive skills, especially speaking, emerge as the most challenging area for students. Reading and writing reflect moderate confidence, suggesting persistent difficulties in academic language processing and production. These patterns reveal that students' affective readiness in academic English is skill-specific and uneven. The study underscores the need for English for Accounting courses to move beyond general language instruction and to incorporate targeted strategies that foster confidence development, particularly in productive academic skills. Such an approach is expected to stregthen students' academic engagement and enhance their readiness for disciplinary communication in higher education contexts.